Pengiriman Tenaga Perawat dan Careworker Indonesia ke Jepang dalam Kerangka Indonesia - Japan Economic Partnership Agreement (IJ-EPA) - Shobichatul Aminah; Stedi Wardoyo; Sri Pangastoeti (Faculty of Cultural Sciences, 2018)
Due to the shortage of professional workers in various felds, Japan began to open up a wide opportunity for the entry of foreign workers by opening various cooperation with other countries to invite the workers to their country. One of them is with Indonesia through a cooperation scheme called IJ-EPA (Indonesia - Japan Economic Partnership Agreement) which includes cooperation in the procurement of manpower feld of nursing. Delivery of nursing workers to Japan certainly has some obstacles, especially related to the complicated requirements to become a nursing staﬀ in Japan, the abilitym to master Japanese and Japanese culture. Terefore, a team of a community engagement of Prodi Jepang, FIB, UGM seeks to help reduce these obstacles through the Socialization of Nurse Competency Standards in the IJ-EPA Framework. Te event was held on 22 November 2017 at Bahrul Ulum Medical School (STIKES), Tambakberas, Jombang, East Java. Te materials given are information about competency standards as required in IJ-EPA, Japanese social and cultural conditions, as well as gemba nihongo or Japanese language used in the nursing profession.